MicroRNA regulation of F-box proteins and its role in cancer. (February 2016) - Wu, Zhao-Hui; Pfeffer, Lawrence M.
Abstract: MicroRNAs (miRNAs) are small endogenous non-coding RNAs, which play critical roles in cancer development by suppressing gene expression at the post-transcriptional level. In general, oncogenic miRNAs are upregulated in cancer, while miRNAs that act as tumor suppressors are downregulated, leading to decreased expression of tumor suppressors and upregulated oncogene expression, respectively. F-box proteins function as the substrate-recognition components of the SKP1-CUL1-F-box (SCF)-ubiquitin ligase complex for the degradation of their protein targets by the ubiquitin-proteasome system. Therefore F-box proteins and miRNAs both negatively regulate target gene expression post-transcriptionally. Since each miRNA is capable of fine-tuning the expression of multiple target genes, multiple F-box proteins may be suppressed by the same miRNA. Meanwhile, one F-box proteins could be regulated by several miRNAs in different cancer types. In this review, we will focus on miRNA-mediated downregulation of various F-box proteins, the resulting stabilization of F-box protein substrates and the impact of these processes on human malignancies. We provide insight into how the miRNA: F-box protein axis may regulate cancer progression and metastasis. We also consider the broader role of F-box proteins in the regulation of pathways that are independent of the ubiquitin ligase complex and how that impacts on oncogenesis. The area of miRNAs and the F-box proteins that they regulate in cancer is an emerging field and will inform new strategies in cancer treatment.